BS EN 4165-013. Aerospace series. Connectors, electrical, rectangular, modular. Operating temperature 175 °C continuous. Part 013. Cable clamp 2 and 4 modules for connectors, series 2 and series 3. Product standard (10th December 2021) - British Standards Institution,
No abstract available